Amplitude characterization of memristive devices - Duarte, João Capela
Memristive Devices (MDs) are usually described by their associated hysteresis loops. Their distinctive memory properties stem from this unusual characteristic, which depends on both stimulus frequency and amplitude. Understanding the behavior of these devices is of paramount importance for a multitude of different applications. This paper investigates the dependency of loop area and length on stimulus amplitude of MDs. The characterization methodology follows the morphological approach, introduced by the authors in [10], for frequency characterization. An example, considering thin film TiO2 MDs reveals that the peak amplitude (amplitude where the loop has maximum area) of the device depends strongly on device dimensions and physical properties.